2015
DOI: 10.2528/pierm15011803
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Antenna Array Configurations Using Far-Field Holographic Microwave Imaging Technique

Abstract: Abstract-Biomedical imaging has played an important role in identifying and monitoring the effectiveness of the current state of the art treatments for many diseases. The authors recently proposed a novel single-transmitter-multiple-receiver holographic microwave imaging (HMI) technique for imaging small inclusion embedded in a dielectric object which has potential application in medical diagnostics. HMI image quality depends highly on the antenna baseline difference, in order words, the antenna array configur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3
1

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Thus, the proposed method has the potential to produce a higher resolution image compared to the conventional EM techniques. Previous experimental studies [ 37 ] have shown that the 2D image quality also depends on the sensor array configuration and the sensor number. However, whether this claim is suitable for the practical 3D HEI system is one of the target future works.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the proposed method has the potential to produce a higher resolution image compared to the conventional EM techniques. Previous experimental studies [ 37 ] have shown that the 2D image quality also depends on the sensor array configuration and the sensor number. However, whether this claim is suitable for the practical 3D HEI system is one of the target future works.…”
Section: Discussionmentioning
confidence: 99%
“…The authors recently developed a holographic microwave imaging technique for breast lesion detection [7], which has the potential to produce a highresolution image. The image quality is improved significantly by using a spiral antenna array [8].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the authors [46] proposed a spiral and random sensor array that contains 16 waveguide antennas for HMI system as shown in Figure 5. The experimental results…”
Section: Microwave Sensor Arraymentioning
confidence: 99%
“…More recently, the authors proposed a far-field HMI method for imaging of biological objects [44][45][46]. Different from IHM, the 3D HMI uses physical displacement (scan of the distance) between the sensor array plane and the imaged object over a specified range (vertical) to obtain the depth information from sequenced 2D images.…”
Section: New Perspectives In Breast Imagingmentioning
confidence: 99%
See 1 more Smart Citation